Cellulose-based hydrogel as halal agricultural medium - Sarah Husnaini Zainal,; Rica Nofrianti,; Azwan Mat Lazim,; Rizafizah Othaman, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Waste paper has been thrown away and caused environmentally problem. Preparation of cellulose-based hydrogel from waste paper has been developed to decrease the pollution since waste paper contains more than 60% of cellulose. Cellulose-based hydrogel is produced from the waste paper solution. To make into hydrogel, the addition of crosslinking agent is needed since hydrogel is defined as a 3D network structure that is crosslinked either chemically or physically. In this study, the waste paper will be treated first to remove impurities. Sodium hydroxide/urea (NaOH/Urea) has been used as a solvent for waste paper dissolution. As hydrogel needed crosslinking to remain the network structure, we used citric acid (CA) as a chemical crosslinking agent and the heating at 60°C and 70°C before and after swelling was studied. The aim of this study is to produce halal soilless agricultural medium using cellulose-based hydrogel media from the waste paper by using non-toxic and environmental friendly solvents and CA as crosslinking agent. Waste paper hydrogel will be characterized via swelling ratio where the highest swelling is about 19% at 70°C heating temperature. Fourier-transform infrared (FTIR) shows a broad band of OH at 3339 cm-1 and another band was shown at 3432 cm-1 for 70°C heating temperature represent OH from the solvent.